New Rock Magnetic Analysis of Ultramafic Cores From the Oman Drilling Project and Its Implications for Alteration of Lower Crust and Upper Mantle. Issue 7 (29th June 2022) - Hong, Gilbert; Till, Jessica Lynn; Greve, Annika; Lee, Sang‐Mook; ,
Abstract: Detailed magnetic analyses of ultramafic rock samples recovered from the Wadi Tayin massif as part of the Oman Drilling Project provide a unique opportunity to understand the magnetic properties of oceanic lithosphere and its alteration since obduction. We examined 300‐ to 400‐m‐long cores from 3 sites (BA1B, BA3A, and BA4A) that transected the crust‐mantle boundary. Serpentinization that produces a small amount of magnetite from olivine alteration plays an important role in shaping the magnetic signature of the rocks recovered from these holes. Our investigation reveals new features, which have not been reported in previous studies of ophiolite largely based on surface rock samples. It appears that when serpentinization reaches a certain point (65%), a sharp increase in magnetic susceptibility occurs. Such pattern opens the possibility of additional production of magnetic minerals induced by various reactions (e.g., further hydration of Fe‐rich serpentine minerals), which may have occurred, while the rocks were being serpentinized. In general, the uppermost section (0–40 m) shows higher susceptibility than the deeper part. Also, higher susceptibility is found in dunite‐dominated sections than those composed of harzburgite. Overall, our observations suggest that mantle rocks of Semail ophiolite have undergone multiple stages of serpentinization over different time periods. Plain Language Summary: Rock magnetic properties have been measured for ultramafic rock samples obtained from cores deep‐drilled from the Wadi Tayin massif as part of the Oman Drilling project. The cores are from 3 drill sites (BA1B, BA3A, and BA4A) where the holes cross the crust‐mantle boundary. An important factor that shapes the rock magnetic properties in the studied samples is serpentinization, the alteration of olivine by interaction with water, as it produces a small amount of magnetite. Our magnetic measurements uncover new properties that have not been reported in previous studies of ophiolite, such as higher magnetic susceptibility near the surface. The large variety observed in magnetic properties may be due to the wide‐ranging degrees of serpentinization. In addition, microscopic observations reveal examples of large magnetite grains appearing along with Fe‐Cr spinel. Overall, our deep drilling study reveals several important features that reflect how magnetic properties are acquired and lost during low‐temperature alteration of lower crust and upper mantle. It also provides a unique representation of the ultramafic sections of oceanic lithosphere, which has not been reached via oceanic deep drilling. Key Points: Our analyses were performed on long cores that were obtained from ophiolite sites via deep drilling as opposed to near‐surface samplings Magnetic susceptibility depends on the degree of alteration and a rough correlation can be seen with the rock type (dunite vs. harzburgite) The findings along the continuous section of ophiolite provide new insights into the magnetization and alteration of lower crust/upper mantle